Genética dos teores de fósforo e de zinco em sementes de feijão - Rosa, Simone Saydelles da (2009)
The common bean (Phaseolus vulgaris L.) stands out as an important source of phosphorus and zinc in for human consumption. Therefore, the legume can be used to reduce the risk of deficiency of phosphorus and zinc and to reduce the number of cases of malnutrition. The objectives of this research were: (1) investigate the presence of maternal effect for phosphorus and zinc contents in common bean; (2) obtain estimates of heritability in early generations. The crossings were performed among cultivars Pérola x Guapo Brilhante and TPS Nobre x Guapo Brilhante. The F1, F1 reciprocal, F2, F2 reciprocal and backcross (RCP1 and RCP2) were obtained. The phosphorus and zinc contents were ascertained by nitric-perchloric digestion and determination on the UV-VIS spectrophotometer (phosphorus) and the atomic absorption spectrophotometer (zinc). The results showed presence of genetic variability for the phosphorus and zinc contents in common bean seeds. No was observed effect maternal significant for phosphorus and zinc contents in common bean seeds. For phosphorus, in the narrow sense heritability of high (65.54%) and low (21.37%) magnitude was obtained. For zinc, estimates of heritability in the narrow sense, high (77.84%) and moderate (57.46%) magnitude were obtained. Transgressive segregation was observed and an increase of 19.17% for the phosphorus content and of 37.26% for the zinc content in common beans seeds was obtained by crop breeding. The selection performed in the early generation may be effective for development of common bean germplasm with higher minerals content.